The Effect of Language Change on the Spoken English of Secondary School Students in Southern Division Ibanda District - Walter, Abemlglsha (Kabale University, 2023)
The study looked at the impact of language change on secondary school students' spoken English Southern Division Ibanda District. The study was guided by the following objectives: to analyse how Ugandan spoken English has changed from its original state to a modern state. to establish the challenges that affect the spoken English of secondary school students in Ibanda, and to propose how English speaking can be improved among secondary school students or the district. The study used both qualitative and quantitative designs. The study used a sample of eighty (80) respondents. A questionnaire was used by the researcher to collect data. The researcher discovered that education and training received the highest percentage, while construction received the lowest percentage, in terms of how Ugandan English has changed from its original state to a modern state. The researcher also discovered that pronunciation had the greatest influence, followed by slangs and idioms. Under the challenges that affect secondary school students' spoken English in the Ibanda district, oquialisrn received the lowest percentage. She also discovered that the largest group suggested that the provision of rules and regulations against mother tongue took the highest percentage, while teachers' involvement in speaking English took the lowest percentage.